Analysis on Conflicts of China's Coal Tax Reform - Wang, Dong (International Journal of Energy Economics and Policy, 2014)
This paper investigates the conflicts which are resulted from coal tax reform in China from economic and public policy perspectives. An analytical framework involving actors, values, interests and institution has been applied. China’s central government eagers to achieve fiscal revenue increase, environmental protection and energy conversation goals by a good governance of coal system. As a traditional and feasible policy instrument, taxation is regarded for dealing with energy issues in politics and governance. However, coal tax reform proposal has induced many controversies in China. The causes of that include value conflicts of all actors, competing interests of all parties and institutional barriers of economic, politics and legislation. Therefore, the government cannot regulate coal issues only through taxation. The case reveals that good governance on coal cannot be achieved only by economic tools as coal system contains so high stake and involves so many players. Keywords: energy tax; coal tax regime; policy instrument; energy conflicts JEL Classifications: H20; Q32; Q38; Q48